Parenting with Metal: Extreme Media Literacy Between Generations - Barratt-Peacock, Ruth (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
Reading interviews published in Canadian magazine Hellbound, I trace a bidirectional dissonance between metal parents’ metal media practices and their role as parents. These “metal parents” address friction between these roles by asserting metal music’s value as a tool for helping children develop mental health management strategies and the media literacy to critically engage with sexual content in other popular media. The latter becomes particularly important in connection to children growing up with metal containing sexual and violent content. Whether we frame it as growing up with metal or raising children with metal, these interviews indicate that there is a significant shift towards intergenerational media practices in consumers of metal music, to which the industry is slowly adapting. Nevertheless, parents appear to still approach metal in the home with ever-shifting compromises and, above all, active engagement between child, parent, and text.